2022
DOI: 10.21203/rs.3.rs-1712584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-nucleus Targeted Peptide Tethered Quadruple Carbon Dots for Treatment of High-grade Gliomas

Abstract: Ultimate goal of the nanomedicine is built on the idea of robust targeted delivery of complex assemblies that contain sufficient amount of multiple therapeutics and diagnostic agents for highly localized payload release with no adverse side effects. Besides the numerous efforts on the field of cancer specific nanomedicine, still there is a great need for improvements in terms of target specificity. Previously, we have reported a target-specific carbon dots- based dual nano-drug delivery system. In study, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As mentioned before, functionalization of CDs is a facile task due to the pre-existing functional groups on the CD surface. Not only can these functional groups contribute to charge transfer during ionization, but they can also help with the solubilization of the analytes by forming polar and nonpolar intermolecular interactions with the analytes during sample preparation, leading to a uniformly dispersed mixture of molecules. , CDs with −NH 2 and −COOH functional groups were synthesized to serve as MALDI matrices for the detection of cholesterol . Computational evaluation of cholesterol interaction with CDs showed that, upon ionization and desorption, the interaction between the carboxylic acid group of CDs and cholesterol was responsible for electron transfer and subsequent loss of a water molecule followed by capturing a proton (Figure ); cholesterol was detected as [M-H 2 O+H] + ionic species (Figure ).…”
Section: Carbon Dotsmentioning
confidence: 99%
“…As mentioned before, functionalization of CDs is a facile task due to the pre-existing functional groups on the CD surface. Not only can these functional groups contribute to charge transfer during ionization, but they can also help with the solubilization of the analytes by forming polar and nonpolar intermolecular interactions with the analytes during sample preparation, leading to a uniformly dispersed mixture of molecules. , CDs with −NH 2 and −COOH functional groups were synthesized to serve as MALDI matrices for the detection of cholesterol . Computational evaluation of cholesterol interaction with CDs showed that, upon ionization and desorption, the interaction between the carboxylic acid group of CDs and cholesterol was responsible for electron transfer and subsequent loss of a water molecule followed by capturing a proton (Figure ); cholesterol was detected as [M-H 2 O+H] + ionic species (Figure ).…”
Section: Carbon Dotsmentioning
confidence: 99%